2019
DOI: 10.3390/medicina55090563
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism rs2066865 in the Fibrinogen Gamma Chain (FGG) Gene Increases Plasma Fibrinogen Concentration and Is Associated with an Increased Microvascular Thrombosis Rate

Abstract: Background and Objective: Thrombosis due to inherited hypercoagulability is an issue that has been raised in microvascular flap surgery previously. We analyzed the association of a single nucleotide polymorphism (SNP) in rs2066865 in the fibrinogen gamma chain (FGG) gene, alteration in plasma fibrinogen concentration, and presence of microvascular flap thrombosis. Materials and Methods: A total of 104 adult patients with microvascular flap surgery were subjected to an analysis of the presence of SNP rs2066865 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There are also newer studies, the results of which indicate a significant role of the FGG polymorphism in the risk of CVD. In a study by Drizlionok et al A/A and G/A genotype carriers of an SNP in rs2066865 in the FGG had a higher plasma fibrinogen concentration, and this might be associated with an increased risk of microvascular thrombosis [ 75 ].…”
Section: Fibrinogen Molecular Modifications and Cardiovascular Riskmentioning
confidence: 99%
“…There are also newer studies, the results of which indicate a significant role of the FGG polymorphism in the risk of CVD. In a study by Drizlionok et al A/A and G/A genotype carriers of an SNP in rs2066865 in the FGG had a higher plasma fibrinogen concentration, and this might be associated with an increased risk of microvascular thrombosis [ 75 ].…”
Section: Fibrinogen Molecular Modifications and Cardiovascular Riskmentioning
confidence: 99%
“…Anyhow, we were not able to avoid the multifactorial nature of a thrombotic event and the human factor in surgery and postoperative care. In microvascular flap thrombosis, both the arterial and venous pools may play a role, which is further augmented by the genetic background of the patients (47,48) or acquired thrombophilia. Therefore, we warrant an appropriate thrombotic risk assessment score for microvascular surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that it might start the coagulation cascade that results in the development of brin clots when its expression rises in response to tissue damage or in ammation. The 261 COVID-19 patients who participated in the previous study showed that individuals with the factor III mutation had signi cantly higher D-dimer levels than those without the mutation [12]. Patients who had the factor III mutation were more likely to pass away than those who did not have the mutation.…”
Section: Introductionmentioning
confidence: 97%
“…Its molecules are 45nm long structures that are composed of two sets of three polypeptide chains: A alpha; B beta; and gamma [11]. Each of these chains is encoded by a separate gene namely, brinogen alpha (FGA), brinogen beta (FGB), and brinogen gamma (FGG), clustered in a region of approximately 50 kb on chromosome 4q31.3 [12]. FGG and FGA are components of brinogen, which are soluble plasma proteins that coagulate into insoluble brin [10].…”
Section: Introductionmentioning
confidence: 99%